2016
DOI: 10.1093/ndt/gfw231
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic risk factors in nondiabetic adolescents with glomerular hyperfiltration

Abstract: Glomerular hyperfiltration is associated with hypertriglyceridemia and increased insulin resistance independent of BMI z- score in a nationally representative sample of US adolescents. Hispanic adolescents are more likely to have hyperfiltration than other racial/ethnic groups. These findings could have significance in evaluations of renal function and MetS in adolescents to identify related risks and target interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 64 publications
1
18
0
Order By: Relevance
“…These findings were surprising and may be hypothesis generating. One hypothesis is that this reflects hyperfiltration, in which the kidney compensates for increased metabolic demands, as noted in obesity[35], insulin resistance[36], MetS[37], and subclinical CVD[38]. This could increase GFR, with initial decrease in CKD.…”
Section: Discussionmentioning
confidence: 99%
“…These findings were surprising and may be hypothesis generating. One hypothesis is that this reflects hyperfiltration, in which the kidney compensates for increased metabolic demands, as noted in obesity[35], insulin resistance[36], MetS[37], and subclinical CVD[38]. This could increase GFR, with initial decrease in CKD.…”
Section: Discussionmentioning
confidence: 99%
“… 23 Moreover, a cross-sectional study of 2584 men and women aged 12–17 years showed that persons with glomerular hyperfiltration (estimated glomerular filtration rate (eGFR)≥120 mL/min 1.73 m 2 ) had higher mean levels of fasting insulin after adjusting for BMI. 24 In that study, eGFR was defined by the Schwartz equation, that is, eGFR (mL/min 1.73 m 2 )=0.413×height (cm)/serum creatinine (mg/dL), so another possibility is that glomerular hyperfiltration led to low serum creatinine levels.…”
Section: Discussionmentioning
confidence: 99%
“…This underscores an enormous risk for future T2DM and CVD based on prevalence of risk factors in the current generation of US adolescents. In addition, MetS is also linked to other obesity-related disease processes, including non-alcoholic fatty liver disease (NAFLD) [51] and renal function [52], with implications for chronic kidney disease [53].…”
Section: Long-term Risksmentioning
confidence: 99%